How Patients With Chronic Liver Diseases Succeed to Deal With COVID-19? - Rezasoltani, Sama; Hatami, Behzad; Yadegar, Abbas; Asadzadeh Aghdaei, Hamid; Zali, Mohammad Reza (Frontiers in Medicine, 2020)
The human pathogenic coronaviruses cause infections of the respiratory tract from mild to severe ranges. Mild cases may look like the common cold, while cases with severe disease may represent severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS) and coronavirus disease 2019 (COVID-19). Currently, COVID-19 is a rapidly emerging infection and the number of COVID-19 cases and its associated deaths are quickly growing around the world. COVID-19 infection can involve multiple body organs other than respiratory tract and lungs such as liver. It is hypothesized that COVID-19-associated liver injury can hamper the host drug metabolism and excretion. Liver involvement present with the elevation of enzymatic levels of alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), and gamma-glutamyl transferase (GGT) accompanied by enhanced total bilirubin and decreased albumin levels has been reported in COVID-19 cases. One of the major concerns during COVID-19 outbreak is the population with a history of pre-existing liver disorders including viral hepatitis, alcoholic liver disease (ALD), non-alcoholic fatty liver disease (NAFLD), autoimmune hepatitis, hepatic compensated, and decompensated cirrhosis. Herein, we discussed the probable correlation between COVID-19 infection and liver damages, particularly chronic and pre-existing liver diseases during COVID-19 outbreak. Furthermore, we explained about the liver transplant recipients and post-transplant drugs used in patients with COVID-19 infection. Finally, we discussed about the therapeutic medications administered in COVID-19 patients with underlying liver injuries and their significant considerations.